225k views
3 votes
How to find the inverse for f(x) = 2x-6

User Sharday
by
4.9k points

2 Answers

6 votes

Answer:


{f}^( - 1) (x) = (x + 6)/(2) \\

Explanation:


f(x) = 2x-6

To find the inverse of f(x) , equate f(x) to y that's


y = 2x - 6

Next interchange the terms that's x becomes y and y becomes x


x = 2y - 6

Next solve for y

Move 6 to the other side of the equation

That's


2y = x + 6

Divide both sides by 2 to make y stand alone


(2y)/(2) = (x + 6)/(2) \\ \\ y = (x + 6)/(2)

We have the final answer as


{f}^( - 1) (x) = (x + 6)/(2) \\

Hope this helps you

User Liesbeth
by
4.7k points
5 votes

Answer:

The inverse is 1/2x +3

Explanation:

f(x) = 2x-6

Replace f(x) with y

y= 2x-6

Exchange x and y

x = 2y-6

Solve for y

Add 6 to each side

x+6 = 2y-6+6

x+6 = 2y

Divide each side by 2

(x+6)/2 = 2y/2

1/2 x+3 = y

The inverse is 1/2x +3

User Gregor Isack
by
5.8k points